2009
DOI: 10.1007/s00038-009-0070-6
|View full text |Cite
|
Sign up to set email alerts
|

Poor social relations and adverse health behaviour: stronger associations in low socioeconomic groups?

Abstract: Given the important role of health adverse behaviour in chronic disease development, results underline the relevance of social environment and socio-economic structure in Public Health interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 16 publications
(12 reference statements)
5
39
2
2
Order By: Relevance
“…The prevalence rate of current smokers (9.0 %) was significantly below the average for the entire country (20.6 % in 2009), the state (22 %), northeast TN and Central Appalachia (28.9 %), and the Southeast USA (range 19-26 %) [1] and is more consistent with prevalence rates reported in studies linking SES with smoking [11,13,29] and other health behaviors [30][31][32][33]. The demographic characteristics (age, gender, and race/ethnicity) of tobacco users in this study, which was confirmed with the proportion of the total sample, appeared to be consistent with those of the general population.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence rate of current smokers (9.0 %) was significantly below the average for the entire country (20.6 % in 2009), the state (22 %), northeast TN and Central Appalachia (28.9 %), and the Southeast USA (range 19-26 %) [1] and is more consistent with prevalence rates reported in studies linking SES with smoking [11,13,29] and other health behaviors [30][31][32][33]. The demographic characteristics (age, gender, and race/ethnicity) of tobacco users in this study, which was confirmed with the proportion of the total sample, appeared to be consistent with those of the general population.…”
Section: Discussionsupporting
confidence: 58%
“…However, social support (Yun, Kang, Lim, Oh, & Son, 2010) and social cohesion (Chuang & Chuang, 2008; Li et al, 2012) may be associated with higher smoking rates in groups with high rates of smoking. Emotional social support (Weyers et al, 2010) and neighborhood social cohesion (Cleland et al, 2010; Cradock, Kawachi, Colditz, Gortmaker, & Buka, 2009; Pabayo, Belsky, Gauvin, & Curtis, 2010; Shelton et al, 2011; Utter, Denny, Robinson, Ameratunga, & Milfont, 2011; Echeverria, Diez-Roux, Shea, Borrell, & Jackson, 2008) are often associated with greater, and loneliness with less (Hawkley, Thisted, & Cacioppo, 2009; Shankar et al, 2011), physical activity, although associations are inconsistent for social support (Debnam, Holt, Clark, Roth, & Southward, 2012; Poortinga, 2006b) loneliness (Lauder et al, 2006) and social cohesion (Ball et al, 2010; Veitch et al, 2012) in similar large, diverse samples. Emotional social support is also associated with greater fruit and vegetable intake (Poortinga, 2006a; Debnam et al, 2012).…”
Section: Introduction1mentioning
confidence: 99%
“…In various studies social relations were shown to be an important health determinant (Berkman and Glass 2000;Cohen 2004;Holt-Lunstad et al 2010;House et al 1988) and a contributing factor to health behaviour (Weyers et al 2010). Generally, structural and functional aspects are distinguished regarding social relations (Berkman and Glass 2000;Cohen 2004).…”
Section: Introductionmentioning
confidence: 99%